A STUDY OF THE FOREIGN LANGUAGE CLASSROOM ANXIETY SCALE (FLCAS): PREVENTING FOREIGN LANGUAGE ANXIETY AMONG UNIVERSITY STUDENTS TO IMPROVE ENGLISH SPEAKING ABILITY - Annisa Nabhan Kamila; Inayah Inayah; Muhammad Ahsanul Husna; Waesama-ae Waemamu; Tuti Qurrotul Aini (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Anxiety when speaking Arabic is a significant challenge for students of the Arabic Language Education Study Program, as it often hinders the development of their speaking skills. This study employed a mixed-methods approach (quantitative and qualitative). Quantitative data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) and analyzed through descriptive statistics, while qualitative data were obtained through unstructured observations and semi-structured interviews and analyzed using a thematic analysis approach. The results indicate that students’ language anxiety levels fall into the fairly high category, with the majority classified as experiencing high anxiety. Dominant forms of anxiety include spontaneous speaking anxiety, social comparison, performance anxiety, and academic-evaluative anxiety, primarily triggered by fear of making mistakes, low self-confidence, and anxiety related to assessment. Students cope with this anxiety through various cognitive, emotional, and social strategies. In conclusion, reducing language anxiety requires a supportive learning environment and instructional strategies addressing learners’ psychological aspects to improve their Arabic speaking performance.